Dual H-bridge integrated multiport DC circuit breaker for bus fault interruption in HVDC grids supporting large-scale renewable energy integration - Qin, Hui; Pan, Zhen; Lu, Yuxin; Zou, Changyue; Qiao, Xuebo; Huang, Yunfeng (Frontiers in Energy Research, 2025)
To address the technical challenge of rapid and reliable interruption of DC faults in offshore wind power DC collection and transmission systems, which are critical for large-scale renewable energy integration, this paper proposes an integrated multi-port DC circuit breaker (DCCB) with bus fault clearing capability based on a dual H-bridge configuration. By extending a pair of bridge arms in the H-bridge to connect to the DC bus and employing diodes in the load commutation switches (LCSs) to form the second H-bridge, the proposed DCCB not only achieves conventional line fault clearing but also has the ability to interrupt bus faults. A five-terminal offshore wind power DC transmission system simulation model was built in PSCAD/EMTDC to verify the performance of the DCCB under various operating conditions. The results demonstrate that the proposed multi-port DCCB can protect multiple DC lines effectively under different conditions.